Trophic ecology of the arboreal and ground ant communities in forests and savannas of central Brazil - Vieira, Jésica; Camarota, Flávio; Vasconcelos, Heraldo L. (Ecological entomology, 2021)
1. The trophic ecology of organisms is often mediated by habitat characteristics. Ants are key organisms of most food webs, and their diet can be plastic depending on the relative availability of different nutrients. 2. Using stable isotope analysis, we investigated whether there were differences in the trophic position (δ15N) and/or in the relative importance of different carbon sources (δ13C) between the arboreal and ground‐dwelling ant communities inhabiting two adjacent and contrasting habitats (savannas and semideciduous forests). 3. Arboreal species on average occupied lower trophic positions (lower δ15N) than did the ground‐dwelling species, as probably in the arboreal stratum there is a prevalence of genera whose species rely heavily on plant and insect exudates. However, regardless of the foraging/nesting strata, there was no difference in mean δ15N between the savanna and forest communities, indicating that differences between these two habitats in the relative availability of sources of protein and carbohydrates for ants are either small or non‐significant. 4. The savanna ant community presented a greater δ13C than did the forest community, as expected, given the high abundance of C4 grasses in savannas. However, the difference in δ13C between the two communities was relatively small, as few savanna species derived most of their carbon from C4‐based food webs. 5. Overall, our study provided important insights into the trophic ecology of ant communities inhabiting contrasting natural habitats, such as different vegetation strata and adjacent forests and savannas. Arboreal ants tend to feed lower in the food chain and on food sources less enriched in 13C than ground‐living species, and differences were equally marked in forests and savannas. Despite the differences in taxonomic composition, forest and savanna ant communities presented a similar trophic structure (similar range and mean of δ15N values). The difference in δ13C between savanna and forest ants was smaller than expected given the much greater abundance of C4 plants in savannas.